Fire resistance tests on steel-to-timber dowelled connections reinforced with self drilling screws - Palma, P. (2013)
The fire performance of timber structures is largely influenced by the behaviour of the connections. Current structural fire design rules for timber connections, according to EN 1995-1-2 [1], are based on a limited number of tests and are only valid for fire resistances up to 30 minutes, for unprotected bolted or dowelled (with d < 12 mm) connections with side member of wood. Improving the fire resistance of timber connections has been the goal of several studies [2–4], which have focused on increasing the thickness of the side members of wood and the end/edge distances of the fasteners or providing additional protection using panels. Another alternative is to overdesign the connections at normal temperature to obtain lower load ratios in fire design, therefore improving the fire resistance. Although effective, these strategies lead to larger crosssections (compromising the whole design) or might not be aesthetically appealing. The reinforcement of timber connections with self-drilling screws has also been addressed in numerous studies [5–9], which focused mainly on preventing brittle perpendicular-to-grain and block shear failures. Reinforcement with self-drilling screws can also, in addition to prevent brittle failure modes, increase ductility and the load-carrying capacity of the connections at normal temperature, by reducing longitudinal splitting and embedment of the fasteners. Since self-drilling screws can be easily inserted and concealed inside timber members, the additional overstrength they provide at normal temperature could be used to improve the fire resistance of timber connections. An experimental campaign was conducted at ETH Zurich and Empa, to characterize the behaviour of timber connections reinforced with self-drilling screws at normal temperature and under fire exposure.